Palestinian Women in Terrorism: a Double-Edged Sword? - Erez, Edna (International journal of offender therapy and comparative criminology, 2020)
Drawing on a decade of research on terrorism in the Israeli-Palestinian conflict, we show how subjective "rational choices" motivate some women to engage in terrorist activism. Focusing on the motives of young women who engage in terrorism is consistent with feminist theory's insistence on women's agency—even at the extremes. In addition to the well-established motivations for terrorism reported in the literature, interviews with young women involved in terrorism reveal mixed personal motives for their gender-defying choices, including thrill-seeking and some conscious rebellion. However, we contend that women's subjective rationale for participation in such violent behavior needs to be contextualized. A cost-benefit approach, we maintain, highlights the strategic considerations supporting the deployment of women as combatants by Palestinian terrorist organizations. We argue that the inclusion of women in terrorist activism in the Israeli-Palestinian conflict exposes a major fault line in attitudes to the role and proper place of women in what remains largely a patriarchal culture. This social ambivalence accounts for why, on all measures, women fare worse than their male counterparts. The implications of the findings for feminist research as well as policy are discussed.